Dinamika Pembelajaran Pendidikan Agama Hindu di Masa Pandemi Covid-19 Di Kelas IV SDN 1 Gadungsari - Ni Made Sukarini; Ni Nengah Selasih (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
The COVID-19 pandemic has had an impact on all areas of life, including education. The coronavirus outbreak has hampered face-to-face learning activities. The learning system is carried out remotely (online) by utilizing information technology. Although there are still many obstacles experienced by both students and educators. On the other hand, learning during this pandemic provides an extraordinary experience for students and educators. Online learning activities insert a sense of dissatisfaction for teachers in distributing material because the implementation of online learning places more emphasis on assignments. Coupled with the lack of interest and motivation to learn from students to read the material, where the learning media through WhatsApp groups is dominated by text messages that cause student learning outcomes to decline.